Keperluan Ijtihad Dan Fatwa Zakat Dalam Skim Bantuan Kos Rawatan Pesakit Jantung Kanak-Kanak Di Malaysia - Azman Ab. Rahman; Afaf Sukari; Nurul Nadia Nozlan; Muhd Faiz Abd Shakor (Akademi Fiqh Islami Malaysia/Islamic Fiqh Academy, 2024)
Vol. 1 No. 1 (2021): Fiqhiyyat - July Issue